The Coloniality of Catastrophe in Caribbean Theater and Performance
XV, 273 p. 7 illus., 4 illus. in color.
Keywords: “This book is essential reading on contemporary pan-Caribbean theater. It is also a fresh take on what it might mean to rethink regional and transnational interconnection through performance. Taken together this rare collection embraces linguistic, national, temporal and geographic differences. They move beyond hackneyed scenarios of the region as a space of perpetual catastrophe and disaster and provoke a reimagination of relations between humans and the more than human world.” --Honor Ford-Smith, York University “Drawing upon plays and performances from the English-, French-, and Spanish-speaking Caribbean this volume both investigates the enduring consequences of colonialism and catastrophe in the region and offers “counter catastrophic” theatrical responses that enable audiences and artists to imagine ways to recuperate and reanimate their communities in the face of catastrophe. The fascinating collection points the way to an understanding of a pan-Caribbean view of theater filled with hope.” --Adam Versenyi, University of North Carolina, Chapel Hill The Coloniality of Catastrophe in Caribbean Theater and Performance calls attention to theater’s capacity to reveal the constructed roots of catastrophe and offer counter catastrophic strategies to live and imagine otherwise. Engaging multilingual theater from across the Caribbean and its diaspora, the essays foster a pan-Caribbean view of theater, identifying shared tropes and theatrical strategies. Essays address 20th and 21st century works that center the relentless cycle of “natural” disasters such as earthquakes, hurricanes, and floods as well as the catastrophic effects of continuing coloniality more broadly. In doing so, they unsettle the normalization of catastrophe. Exploring the power of theater’s situatedness, its iterative quality, and its special arrangement of time, these works remind us of the impact of embodied co-presence in the political realities of everyday life. Camilla Stevens is Professor in the Departments of Spanish and Portuguese and Latino and Caribbean Studies at Rutgers University-New Brunswick, United States. Jon D. Rossini is Professor in the Department of Theatre and Dance at the University of California, Davis, United States.